Torpedoed : the true story of the World War II sinking of "The Children's Ship" - Heiligman, Deborah (Godwin Books, 2019)
Recounts the attack on passenger ship SS "City of Benares" during WWII, which was carrying nearly 100 British children escaping from the German onslaught of England's major cities as part of the Children's Overseas Reception Board program. As their military escort departed on the way to Canadian ports, a German submarine torpedoed the ship, not knowing it was a civilian ship carrying children. The author draws on first-hand accounts of the tragedy, providing backstories of the children and chaperones while also documenting their experiences. Includes extensive backmatter including interviews.